Potassium Increases Nitrogen and Potassium Utilization Efficiency and Yield in Foxtail Millet - Meiqiang Yin; Yanfen Li; Qilin Hu; Xiangjun Yu; Mingjing Huang; Juan Zhao; Shuqi Dong; Xiangyang Yuan; Yinyuan Wen (Agronomy, 2023)
Field experiments were conducted to investigate the effects of K application on the nitrogen and potassium utilization efficiency and yield of foxtail millet (Setaria italica L.). The experiment was performed with a completely randomized design with two millet cultivars (Jingu 21 and Zhangza 10) and five K2O rates (0, 60, 120, 180, and 240 kg/hm2) in 2020 and 2021. We found that K promoted K and N absorption; significantly increased dry matter (DM), N, and K accumulation in millet organs; caused dry matter accumulation to peak earlier; and increased the DM accumulation rate. In addition, K accumulation preceded that of DM or N. Relative to the crop cycle, most K (61.07%) accumulated at booting, whereas N accumulated mostly (33.86%) during grain filling. N absorption efficiency increased by 31.87%, and the apparent and agronomic utilization rate of K fertilizer remained high, increasing millet yield, which peaked at a K rate of 180 kg/hm2 for both cultivars, by 29.91% and 31.51% in Jingu 21 and Zhangza 10, respectively, relative to untreated controls. Stepwise regression and path analysis showed that the leaf and spike K accumulation, stem N accumulation, and stem DM were the main factors affecting yield, with DM having the greatest direct effect, followed by leaf K accumulation. The K concentration (0.77–3.04%) in Zhangza 10 was higher than that in Jingu 21 (0.69–2.91%) in untreated plants. Under the same K application rate, N and K accumulation and the harvest index were higher for Zhangza 10 than those for Jingu 21, and the nutrient utilization ability was greater for Zhangza 10. The results demonstrated that rational K fertilizer application can increase K concentration and accumulation in leaves, promote N metabolism and accumulation, increase N and K utilization efficiency, and improve DM accumulation and millet yield.